Guaiazulene Triggers ROS-Induced Apoptosis and Protective Autophagy in Non-small Cell Lung Cancer - Ye, Qin; Zhou, Li; Jin, Ping; Li, Lei; Zheng, Shuwen; Huang, Zhao; Liu, Jiayang; Qin, Siyuan; Liu, Hao; Zou, Bingwen; Xie, Ke (Frontiers in Pharmacology, 2021)
Non-small cell lung cancer (NSCLC) is one of the most frequent cancers worldwide, yet effective treatment remains a clinical challenge. Guaiazulene (GYZ), a cosmetic color additive, has previously been characterized as a potential antitumor agent due to observed anticancer effects. However, the efficacy of GYZ in the treatment of NSCLC and the involved molecular mechanisms remain largely unknown. Here, we indicated a role for GYZ in the suppression of NSCLC both in vitro and in vivo via triggering reactive oxygen species (ROS)-induced apoptosis. Concomitantly, GYZ induced complete autophagic flux in NSCLC cells via inhibiting the Akt/mTOR signaling pathway, which displayed cytoprotective effect against GYZ-induced growth suppression. Accompanied with autophagy inhibition obviously enhanced the effects of GYZ. Notably, GYZ acts synergistically with paclitaxel in the suppression of NSCLC in vitro. Together, our results for the first time reported that GYZ suppressed the proliferation of NSCLC and suggested a potential strategy for inhibiting NSCLC growth by combinational use of GYZ and autophagy inhibitors.